Tribological Properties of Al-Based Composites Reinforced with Fullerene Soot - Firuz Yunusov (MDPI AG, 2021)
Aluminum-based composite materials reinforced with fullerene soot, which is a mixture of fullerene and amorphous carbon, are promising materials for friction and wear applications. Composite materials: aluminum with 2% fullerene soot (f.s) and Al with 2% f.s and 2% Cu were obtained via mechanical milling followed by hot pressing. The tribological properties (friction and wear) of the listed composites were investigated and compared with the results for pure aluminum obtained under similar conditions. It has been shown that the addition of fullerene soot reduces the friction coefficient by 25%. At additional alloying with copper, the friction coefficient decreased by 35% in comparison with pure aluminum and also lad to a decrease in friction fluctuations. The wear rate of composite Al with 2% f.s decreased twice in comparison with that of pure aluminum, and with additional alloying it decreased 2.5 times. The morphology of the wear surfaces was investigated by scanning electron microscopy (SEM). The influence of fullerene soot and additional alloying on the wear mechanism was shown.